Pharmacokinetics and Macrophage Inhibitory Cytokine‐1 Pharmacodynamics of the Murine Double Minute 2 Inhibitor, Navtemadlin (KRT‐232) in Fed and Fasted Healthy Subjects. Issue 5 (16th February 2022) - Wong, Shekman; Krejsa, Cecile; Lee, Dana; Harris, Anna; Simard, Emilie; Wang, Xiaohui; Allard, Martine; Podoll, Terry; O'Reilly, Terry; Slatter, J. Greg
Abstract: This single 60‐mg dose, 4‐period crossover study assessed the effect of food and formulation change on navtemadlin (KRT‐232) pharmacokinetics (PK) and macrophage inhibitory cytokine‐1 (MIC‐1) pharmacodynamics. Healthy subjects (N = 30) were randomized to 3 treatment sequences, A: new tablet, fasted (reference, dosed twice); B: new tablet, 30 minutes after a high‐fat meal (test 1); C: old tablet, fasted (test 2). PK/pharmacodynamic parameters were measured over 0 to 96 hours. Adverse events were mild without any discontinuations. No serious adverse events or deaths occurred. In treatment A, navtemadlin mean (coefficient of variation) maximum concentration (Cmax ) was 525 (66) ng/mL, at median time to maximum concentration (tmax ) of 2 hours. Mean (coefficient of variation) area under the plasma concentration–time curve from time 0 to time t (AUC0‐t ) was 3392 (63.3) ng h/mL, and arithmetic mean terminal half‐life was 18.6 hours. Acyl glucuronide metabolite (M1)/navtemadlin AUC0‐t ratio was 0.2, and urine excretion of navtemadlin was negligible. After a meal (B vs A), navtemadlin tmax was delayed by 1 hour. Geometric least squares means ratios (90%CI) for navtemadlin Cmax and AUC0‐t were 102.7% (87.4‐120.6) and 81.4% (76.2‐86.9), respectively. Old vs new tablet fasted formulations (C vs A) had geometric least squares means ratios (90%CI) of 78.4% (72.0‐85.3) for Cmax and 85.9% (80.5‐91.7) for AUC0‐t . MIC‐1 Cmax and AUC were comparable across groups; tmax was delayed relative to navtemadlin tmax by ≈8 hours. Navtemadlin AUC0‐t and MIC‐1 AUC0‐t correlated significantly. In conclusion, navtemadlin can be administered safely with or without food; the new formulation does not affect navtemadlin PK. The 60‐mg navtemadlin dose elicited a reproducible and robust MIC‐1 response that correlated well with navtemadlin exposure, indicating that murine double minute 2 target engagement leads to p53 activation.